If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(8-k)/5=6
We move all terms to the left:
(8-k)/5-(6)=0
We add all the numbers together, and all the variables
(-1k+8)/5-6=0
We multiply all the terms by the denominator
(-1k+8)-6*5=0
We add all the numbers together, and all the variables
(-1k+8)-30=0
We get rid of parentheses
-1k+8-30=0
We add all the numbers together, and all the variables
-1k-22=0
We move all terms containing k to the left, all other terms to the right
-k=22
k=22/-1
k=-22
| 8-k/5=2 | | 1/2(2-4x)2x=13 | | -5=5+z | | 0.15=y-0.450.15 | | 3p/12=6 | | 6m+3+9=2m-6-m | | -3+5y=-38 | | 4-3x/3=7 | | 4k-21=65 | | y/30-21=39 | | 7=2f | | (2x+3)(2x+5)=(2x+3)(2x+5) | | 84=6(c-81) | | 8x+1=3x×20 | | (2x+3)(2x+5)=x | | 90=9(u+8) | | -14=-20=n | | 9(r-91)=18 | | -16=-17+m | | z/6+32=36 | | 20-2w=6 | | 3.56+7.56x+9.12=50.85 | | 15p-9=2p+12 | | -13=n-7 | | x/3/4=7/5/7/15 | | 4=r/5-3 | | 8f-14=42 | | -5k=-5.65 | | 37=3v-38 | | 49/v=7 | | 5q-14=51 | | 63=15+4z |